Climatic water budget between Erbil, Sulaymaniyah and Dohuk station - Sanaa Abdul baqi Bakir (Zanco Journal of Humanity Sciences)
The aim of this study is to investigate the effect of climate elements on the climatic water budget in Erbil, Sulaymaniyah and Dohuk station by using mathematical equations to extract the budget water  values ​​(surplus or water deficit) of these stations. With knowledge of the differences in surplus and water deficit between the stations of the study area.